Information Literacy Skills of Library Users in Utilizing Digital Information Resources at the Library of Universitas Negeri Padang in 2025 - Dhea Lovelinessia; Elva Rahmah (Darul Yasin Al Sys, 2026)
The increasing use of digital information resources in higher education requires students to possess adequate information literacy skills to support academic activities. This study aims to analyze the information literacy skills of library users in utilizing digital information resources at the Library of Universitas Negeri Padang. A descriptive quantitative approach was employed, involving 98 respondents selected through simple random sampling. Data were collected using a questionnaire and analyzed through descriptive statistics. The findings show that the information literacy skills of library users were in the high category, with a mean score of 3.13, equivalent to 78.24%. All measured indicators, namely identifying information needs, searching and accessing digital information, evaluating digital information, and using information effectively and ethically, were also categorized as high. The indicator of effective and ethical information use obtained the highest score, whereas searching and accessing digital information received the lowest score, although it remained within the high category. This study concludes that library users have strong information literacy skills in utilizing digital information resources to support academic activities. The findings contribute to the development of information literacy studies in academic library contexts and provide practical implications for university libraries in strengthening information literacy programs, particularly those related to the use of academic digital information resources.